Book review: Harvey, P. and Knox, H. 2015: Roads: An Anthropology of Infrastructure and Expertise. (April 2017) - Menezes, Deborah
Harvey, P. and Knox, H. 2015: Roads: An Anthropology of Infrastructure and Expertise . New York: Cornell University Press. xiv + 239 pp. 79.95. ISBN: 9780801453236 (Hardcover). 26.95. ISBN: 9780801479649 (Paperback).